Giving Moringa Leaf Noodle and Eel Formulations on Body Weight as an Effort to Prevent Stunting in Toddler - Usman, Usman; Sulaiman, Zulkarnain; Suherman, Suherman; Umar, Fitriani (Sarana Ilmu Indonesia (salnesia), 2024)
The issue of stunting continues to pose a threat to the future generation of Indonesia. Local plants with high nutritional content include moringa leaves. Apart from moringa leaves, eels also have high nutritional value. Innovation in the formulation of noodle combining moringa leaves and eels is highly needed as a functional food for stunting prevention. The research aimed to determine the level of acceptance of subjects towards the formulation of moringa leaf and eel combination noodles and to assess the effectiveness of the noodle formulation in increasing or changing the weight of toddlers. A pure experimental study with an RAL design was conducted in July-August 2023, involved 30 toddlers and 30 mother-toddler subjects selected through purposive sampling. Data analysis included organoleptic tests to measure the subjects' preferences for the noodle formulation and Paired sample t-test to assess the impact of the noodle formulation on changes in toddlers' weights. The research findings indicated that on average, mothers' preferences for moringa leaf and eel noodles, particularly in terms of color and texture, received positive ratings, while aroma and taste were rated moderately positive. The toddlers' weights before consuming moringa leaf and eel noodles was 9,73 kg, and after consumption, the average weight increased by 0,48 kg to 10,21 kg. The research conclusion confirms that the moringa leaf and eel noodle formulation are potential to have a positive impact on increasing toddlers' weights.